Comparison of Voter Participation among Generation Z, Millennial Generation, Generation X, and Baby Boomers in the 2024 General Election - Syukur, Iskandar; Octafiona, Era; Putri, Gita Leviana; Kesuma, Mezan el-Khaeri (GoAcademica Research & Publishing, 2025)
The objective of this study is to analyze the comparison of voter participation among Generation Z, Millennials, Generation X, and Baby Boomers in the 2024 General Election in Lampung Province. This study employs a quantitative method with a survey approach, where the population consists of 6,539,128 registered voters, and a sample of 2,085 respondents is selected using the Slovin formula. Data were collected through a questionnaire designed to measure political knowledge, attitudes toward elections, and political participation. The discussion results indicate a significant difference in voter participation levels across generations. Generation Z exhibits a lower participation rate compared to other generations, influenced by a lack of political knowledge and interest in political issues. Meanwhile, Millennials and Generation X demonstrate more active participation, driven by an awareness of the importance of their votes in shaping policy direction. The conclusion of this study emphasizes that to enhance voter participation, particularly among Generation Z, more intensive political education efforts and effective communication strategies from political parties are needed. This study provides valuable insights for policymakers and political parties in designing programs that can improve voter participation in the future.